Emotion and Implicit Timing: The Arousal Effect - Droit-Volet, Sylvie; Berthon, Mickaël (Frontiers in Psychology, 2017)
This study tested the effects of emotion on implicit time judgment. The participants did not receive any overt temporal instructions. They were simply trained to respond as quickly as possible after a response signal, which was separated from a warning signal by a reference temporal interval. In the testing phase, the inter-signal interval was shorter, equal or longer than the reference interval and was filled by emotional pictures of different arousal levels: high, moderate, and low. The results showed a U-shaped curve of reaction time plotted against the interval duration, indicating an implicit processing of time. However, this RT-curve was shifted towards the left, with a significantly lower peak time for the high-arousal than for the low-arousal emotional pictures. This emotional time distortion in an implicit timing task suggests an automatic effect of emotion on the internal clock rate.